Gamæstética: reflexões sobre games, arte, estética e processos criativos - Mendonça, Bruno de Abreu (2022)
GAMÆSTHETICS: Reflections on Games, Art, Aesthetics and Creative Processes is a propo-sal for the application of a specific aesthetic theory/approach – developed here – to be adop-ted when dealing with video games and gameart objects, seeking to preset an understanding and analysis of the details that embody player’s experience. It is a research aimed mainly at understanding the visualities addressed in video games and gameart, what they refer to and how they create bonds with those who interact with them, having here considered how com-mon – and, why not, necessary – these electronic games have become within the contempo-rary social structure. The studies developed here permeate the fields of art, game design, visualities and philosophy, presenting discussions and concepts that act in a supplementary way to the very existence of electronic games. These, allied to the basis of argument that brings to light the indispensable link between the theoretical act and the process of creating the poetics of the ludic object, aim at a direct approximation with the term gamæsthetics, coined here as the study of the act of playing and how the player interprets it. In this thesis, gamæsthetics is conceptualized from theoretical-practical creation exercises, observing what is behind the game, in addition to bits and pixels. It is an action of sifting through motivations and intentions defined (consciously or not) by aesthetic options and extracting from there the understanding of expression, of feeling; it is to insert oneself in the game and to be part of it.